2014
DOI: 10.1080/00319104.2013.876639
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of liquid Co–Sn alloys: thermodynamic evaluation and experiment

Abstract: Shear viscosity measurements were performed for liquid Co–Sn alloys over a wide temperature range above the respective liquidus temperatures. A high temperature oscillating-cup viscometer was used. It was found experimentally that viscosity as a function of temperature obeys an Arrhenius law. The data were compared with calculated values, obtained from different thermodynamic approaches. A good agreement was found between experimental results and calculated ones by the Budai–Benkö–Kaptay model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…It should be noted that several Co-based systems reveal significant structure transformations with the concentration and composition changes in the liquid state [15] . Such structure anomalies bring to deviations of the structure sensitive properties from the ideal behavior: the concentration dependence of the activation energy of viscous flow of liquid Co–Sn alloys is similar to the liquidus curve of the phase diagram and shows an unexpected increase near the eutectic concentration [17] ; the surface tension data versus concentration have a negative deviation from the Raul’s law at 1823 K [18] . Besides, the enthalpy of mixing shows the temperature dependence with more negative values at lower temperatures [19] .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that several Co-based systems reveal significant structure transformations with the concentration and composition changes in the liquid state [15] . Such structure anomalies bring to deviations of the structure sensitive properties from the ideal behavior: the concentration dependence of the activation energy of viscous flow of liquid Co–Sn alloys is similar to the liquidus curve of the phase diagram and shows an unexpected increase near the eutectic concentration [17] ; the surface tension data versus concentration have a negative deviation from the Raul’s law at 1823 K [18] . Besides, the enthalpy of mixing shows the temperature dependence with more negative values at lower temperatures [19] .…”
Section: Introductionmentioning
confidence: 99%
“…In the Co-Sn system [18], it was shown that the viscosity of the molten Co-Sn increases with an increase in the amount of cobalt (the higher melting point metal) present in the melt. We therefore suggest that the Co-Zn system behaves similarly, with higher viscosity Co-Zn forming in the case of smaller scrap parts (Co-rich), and lower viscosity (Zn-rich) melts forming in the case of larger scrap that is not fully zinc infiltrated.…”
Section: Resultsmentioning
confidence: 99%
“…Also, from practical point of view, viscosity is reported to be one of the key parameters for design and optimisation of metallurgical processes [39]. In addition, Gruner et al in [40] reported that, a study of viscosity of liquid alloys will contribute to the understanding of the relations between atomic structure and physical properties of alloys since properties like viscosity and diffusion are strongly sensitive to structural changes with respect to temperature and composition.…”
Section: Surface Properties Modelmentioning
confidence: 99%